Nutritional Habits and Weight Status among Jazan University Students: Eating Patterns and Healthy lifestyle Assessment (Epidemiology, Biostatistics, and Public Health, 2022)
ObjectivesThe purposes of this study were to assess the prevalence of underweight, overweight, and obesity and to evaluate the nutritional habits, and related factors among the Students of Jazan University.MethodsThis cross-sectional study was carried out during the academic year 2014/2015 in Jazan University, Gizan, South West Saudi Arabia. A total of 436 students 19–25 y of age were examined. The questionnaires, including items on eating habits, lifestyle, and socio-demographic characteristics, were completed by the students. Data on weight, height were also collected.  The data were analyzed using descriptive statistics and chi-square test. Differences were considered statistically significant at P. value  < 0.05.ResultsThe mean weight for males and females were 67.84 and 54.79 kg respectively, with significant differences between males and females (P. value
Keywords: Body mass index; Cross-sectional study; underweight; Jazan; overweight